2018
DOI: 10.1029/2018ja025721
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Low‐Altitude Ionospheric Upflow by Linear and Nonlinear Atmospheric Gravity Waves

Abstract: This study examines how thermospheric motions due to gravity waves (GWs) drive ion upflow in the F region, modulating the topside ionosphere in a way that can contribute to ion outflow. We present incoherent scatter radar data from Sondrestrom, from 31 May 2003 which showed upflow/downflow motions, having a downward phase progression, in the field‐aligned velocity, indicating forcing by a thermospheric GW. The GW‐upflow coupling dynamics are investigated through the use of a coupled atmosphere‐ionosphere model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 87 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…Burleigh et al. (2018) showed that TID changed the collision frequency of the ionosphere by modulating the electron density, thus leading to the increase or decrease in the electron temperature, and finally driving ion upflow or downflow through the ambipolar electric field. Additionally, solar flares can influence the characteristics of traveling atmospheric disturbances or existing TID (Helmboldt et al., 2015; Qian et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burleigh et al. (2018) showed that TID changed the collision frequency of the ionosphere by modulating the electron density, thus leading to the increase or decrease in the electron temperature, and finally driving ion upflow or downflow through the ambipolar electric field. Additionally, solar flares can influence the characteristics of traveling atmospheric disturbances or existing TID (Helmboldt et al., 2015; Qian et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Traveling ionospheric disturbances (TIDs) are common features of the ionospheric F-region, which are fluctuations of the electron density caused by the excitation of atmospheric gravity waves (Francis, 1974;Hines, 1960). Burleigh et al (2018) showed that TID changed the collision frequency of the ionosphere by modulating the electron density, thus leading to the increase or decrease in the electron temperature, and finally driving ion upflow or downflow through the ambipolar electric field. Additionally, solar flares can influence the characteristics of traveling atmospheric disturbances or existing TID (Helmboldt et al, 2015;Qian et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This multi‐fluid description is coupled to a quasi‐static description of auroral and neutral dynamo electric currents. Well suited to modeling sounding rocket campaigns, data inputs used to drive and constrain GEMINI‐TIA can include perpendicular electric fields, characteristic energy and total energy flux from electron precipitation (Burleigh et al., 2019), neutral winds (Burleigh et al., 2018), and wave heating from broadband extremely low frequency (BBELF) waves (Burleigh & Zettergren, 2017).…”
Section: Ionospheric Modelmentioning
confidence: 99%
“…Inputs for GEMINI‐TIA include topside ionospheric potential, electron precipitation, power spectral density from BBELF waves, and neutral winds (Burleigh et al, ). For this study, GEMINI‐TIA is initialized only with data‐inspired precipitation and DC electric field values to mimic the effects of the observed PMAFs.…”
Section: Ionospheric Modelmentioning
confidence: 99%